Konstitusi dan Keamanan Siber Layanan Publik: Kekosongan Regulasi AI sebagai Ancaman terhadap Hak atas Rasa Aman dan Perlindungan Data Pribadi - linda widianti (Yayasan Lentera Keadilan Cendikia, 2026)
This article examines the constitutional implications of deploying artificial intelligence (AI) in Indonesian public services from the perspectives of cybersecurity and personal data protection. While digital public services may improve efficiency and responsiveness, the increasing use of AI systems also expands cybersecurity risks, amplifies large-scale personal data processing, and creates accountability gaps when algorithmic outputs affect administrative actions. This study aims to analyze how the regulatory vacuum on AI governance can threaten the constitutional right to a sense of security and weaken personal data protection in public service delivery, and to propose a legally accountable regulatory direction. Using a normative legal method with a statute approach and a conceptual approach, the research analyzes constitutional principles, relevant statutory frameworks on electronic systems and data protection, and legal concepts of transparency, accountability, and state responsibility. The findings indicate that existing rules remain fragmented and are not sufficiently specific to regulate AI-related obligations such as risk assessment, auditability, minimum transparency/explainability, human oversight for high-impact decisions, and effective remedies for citizens harmed by data breaches or erroneous automated outcomes. Therefore, the article recommends a risk-based AI governance framework for public services that integrates cybersecurity safeguards, clear liability allocation, incident response standards, and accessible mechanisms for objections and redress to ensure constitutional compliance in the digital era.